Solid State Fermentation of Olive Leaves as a Promising Technology to Obtain Hydroxytyrosol and Elenolic Acid Derivatives Enriched Extracts - Anna Starzyńska-Janiszewska; Carmen Fernández-Fernández; Beatriz Martín-García; Vito Verardo; Ana María Gómez-Caravaca (MDPI AG, 2022)
Extraction of valuable bioactive compounds from olive leaves is a hot topic and the use of sustainable and green technologies is mandatory in terms of circular economy. In this way, the use of fermentation technologies showed very interesting results in terms of phenolic compound recovery. Because of that in this work the use of solid state fermentations, as valuable tool to improve the phenolic extraction has been checked. Aspergillus oryzae (in mycelium and spore form), Aspergillus awamori and Aspergillus niger were used as fermentation microrganisms. Phenolic compounds were determined by HPLC-ESI-TOF-MS and, to our knowledge, new compounds have been tentatively identified in olive leaves. Fermentation using mycelium of Aspergillus awamori, Aspergillus niger and Aspergillus oryzae were effective to increase both hydroxytyrosol and elenolic acid derivatives whereas the use of spores of Aspergillus oryzae caused a loss of hydroxytyrosoyl derivatives, contrary the content of elenolic derivatives are comparable with the other fermentation treatments and higher than control. The proposed fermentation processes using the mycelium of Aspergillus awamori, Aspergillus niger and Aspergillus oryzae lead to an increase the hydroxytyrosyl and elenolic acid derivatives and could be used at industrial scale to obtain enriched extracts.